3(4Z-1)-4(Z+8)=3(Z+1)

Simple and best practice solution for 3(4Z-1)-4(Z+8)=3(Z+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(4Z-1)-4(Z+8)=3(Z+1) equation:


Simplifying
3(4Z + -1) + -4(Z + 8) = 3(Z + 1)

Reorder the terms:
3(-1 + 4Z) + -4(Z + 8) = 3(Z + 1)
(-1 * 3 + 4Z * 3) + -4(Z + 8) = 3(Z + 1)
(-3 + 12Z) + -4(Z + 8) = 3(Z + 1)

Reorder the terms:
-3 + 12Z + -4(8 + Z) = 3(Z + 1)
-3 + 12Z + (8 * -4 + Z * -4) = 3(Z + 1)
-3 + 12Z + (-32 + -4Z) = 3(Z + 1)

Reorder the terms:
-3 + -32 + 12Z + -4Z = 3(Z + 1)

Combine like terms: -3 + -32 = -35
-35 + 12Z + -4Z = 3(Z + 1)

Combine like terms: 12Z + -4Z = 8Z
-35 + 8Z = 3(Z + 1)

Reorder the terms:
-35 + 8Z = 3(1 + Z)
-35 + 8Z = (1 * 3 + Z * 3)
-35 + 8Z = (3 + 3Z)

Solving
-35 + 8Z = 3 + 3Z

Solving for variable 'Z'.

Move all terms containing Z to the left, all other terms to the right.

Add '-3Z' to each side of the equation.
-35 + 8Z + -3Z = 3 + 3Z + -3Z

Combine like terms: 8Z + -3Z = 5Z
-35 + 5Z = 3 + 3Z + -3Z

Combine like terms: 3Z + -3Z = 0
-35 + 5Z = 3 + 0
-35 + 5Z = 3

Add '35' to each side of the equation.
-35 + 35 + 5Z = 3 + 35

Combine like terms: -35 + 35 = 0
0 + 5Z = 3 + 35
5Z = 3 + 35

Combine like terms: 3 + 35 = 38
5Z = 38

Divide each side by '5'.
Z = 7.6

Simplifying
Z = 7.6

 

See similar equations:

| -3(4s-1)-3=-2(9s+0)-2 | | 10+x+x=3x+x | | 8+j=3 | | 4x-4x=6 | | 8x+6=3x-4 | | 3m+4=-2 | | 24-6n=6(4+5n) | | -9=n+8n | | 6(2n-5)=4n+2 | | 5a+3=3a+4 | | 17+x=-24 | | 2d+18=60 | | 47=7x-9 | | -6x-12y=13 | | 11a^2-4a+7=0 | | 2(3x+4)-2x=x+20 | | 2(x+3)+3x=2x+15 | | 3x+2y=-30 | | 6a+2=3a+4 | | 6x-1=48-x | | 6x^3+3x^2+8x+4=0 | | 14-(6x-5)=(2x-1)-4x | | 50x^2+60x=0 | | 6+x=9(x-5) | | 3990=2.5x | | y=x^5-15x^3 | | 553+47+30+68+35+45= | | 0.5a+9=2a-6 | | y=4-2*-3 | | y=2x^3-3x^2-36x+9 | | 90y+36-72y=30 | | 0=x^2-x-12 | | x-19.7=-17.48 | | 15z-4=7z+36 | | -4-11+17*4=53 | | 2x^2+5=31 | | 25x+10x+7=0 | | 100x^2=49 | | m^2+2m+6=0 | | x^2-40=3x | | -3x^2+42x-147=0 | | ln(x+9)+ln(x-4)=2ln(x) | | 36x^2-225=0 | | 0.5(-4+6x)=0.3x+0.67(x+9) | | 18z+3=9z+48 | | p+-2=21 | | 8x+4x+5x=7 | | 0.6x=-9 | | 7(2+3x)+8= | | 3m^2=3-8 | | 1.32+1.5=5.4 | | 3m^2=3-8m | | 5z+58=14z+4 | | 9+5(4x+4)= | | 0.3=-6 | | 0.03=3.5c-1.02 | | 12+3(8+x)= | | 2x^2+3x=81 | | (7x+2)3+8x= | | 6(4x+7)+x= | | 2(2t-5)+t=2-t | | x^2+2x+1=81 | | 96=-16t^2+96t | | 3x+(2x+6)5= | | -7k+6k=10 |